Flexural strengthening of RC slabs with prestressed CFRP strips using different anchorage systems - Correia, Luís (2014)
In the field of flexural strengthening of concrete structures the Externally Bonded Reinforcement (EBR) technique using carbon fiber-reinforced polymers (CFRP) is commonly used. This technique offers several structural advantages when the CFRP material is prestressed. One of the critical aspects of a prestressing technique is the type of end anchorage. Two systems are investigated in the present paper: the metallic anchorage elements fixed to the ends of the FRP reinforcement and the gradient anchorage. In order to assess the performance of these two systems, an experimental program was carried out. In addition to the anchorage systems, the cross-section geometry of the CFRP strip was also included in this study. Eight slabs were monotonically tested under displacement control up to failure by using a four-point bending test configuration. The observed performance of the tested slabs is critically analyzed.